The Residential School Settlement with Yukon First Nation survivors : a positive form of relationship renewal? - Edelman, Spencer James (Lethbridge, Alta. : University of Lethbridge, Faculty of Health Sciences, c2012, 2012)
vii, 117 leaves 29 cm Reconciliation attempts have occurred world-wide, i.e., Australia and South Africa. Recently, Canada has initiated a reconciliation process with its First Nations people for the historical injustices and their experience with residential schools. The purpose of this study was to explore the current Canadian reconciliation process and to determine whether it was considered by First Nations participants as an effective approach to relationship renewal. This study was completed with the White River First Nations in the Yukon Territory. Using an exploratory descriptive design as a qualitative approach, with person-centered interviewing, eight participants were interviewed twice. The data revealed that the current reconciliation process was driven by political expediency rather than anchored by a desire to improve relationships. The findings suggest that Canada’s reconciliation model is unsuitable and may be at risk for failure in the near future. Finally, participants revealed that they wanted more healing as a step towards reconciliation.